2013
DOI: 10.4317/medoral.18425
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo study of bacterial coronal leakage in indirect pulp treatment

Abstract: Objective: The aim of this study was to evaluate, ex vivo, bacterial coronal leakage with different antimicrobial agents applied to the dentine for indirect pulp treatment (IPT). Study Design: Sixty extracted teeth were prepared and randomly distributed into 5 groups (n=10): Group 1: no antimicrobial dentine treatment; group 2: 1% chlorhexidine (CHX)+1% thymol varnish (Cervitec®); group 3: 2 % CHX solution; group 4: 40% CHX varnish (EC40™) and group 5: Clearfil™ Protect Bond (CPB). Ten teeth served as control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In addition to its antimicrobial effect, several studies found that using CHX with polyacrylic acid increased the GIC bond strength [ 31 – 34 ]. CHX neutralized the dentin surface that was applied with an acid conditioner [ 33 ] and also increased the surface energy of the dentin [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its antimicrobial effect, several studies found that using CHX with polyacrylic acid increased the GIC bond strength [ 31 – 34 ]. CHX neutralized the dentin surface that was applied with an acid conditioner [ 33 ] and also increased the surface energy of the dentin [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…CHX is a well-known antimicrobial agent that is frequently used as a cavity disinfectant to prevent pulpitis caused by bacteria after selective caries removal (77,94,95). Several other studies also showed that application of CHX prior to GI restoration helped improve bond strength (29)(30)(31)(32). Shear bond strength of H-GIC was superior in CHX treated groups compared with control group which increased success rate in the long term (32).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the antimicrobial effect, several studies found that using CHX with polyacrylic acid helps to create desirable bond ability of GIC (29)(30)(31)(32). CHX helps to neutralize the dentin surface that is applied by an acid conditioner (31) and also increases the surface energy of the dentin (31).…”
Section: Background and Rationalementioning
confidence: 99%
See 2 more Smart Citations